OPPORTUNITIES FOR INTEGRATING JAPANESE EXPERIENCE INTO UZBEKISTAN’S HIGHER EDUCATION SYSTEM - Jakbarov Odiljon Otamirzaevich (Web of Journals Publishing, 2025)
This article examines the key aspects of Japan’s higher education system and the possibilities of adapting them to Uzbekistan’s higher education system. The study explores Japan’s education quality, innovative teaching approaches, university-industry collaboration, and personnel training system. Recommendations for applying Japanese experience in Uzbekistan are proposed.
Keywords: Japanese higher education, innovative education, university-industry collaboration, education quality, Uzbekistan’s education system.